Effect of forest cover in agricultural landscapes on pollinator abundance in homesteads - Krishnan, Abhiram; Gopika Viswan, Hariraveendra; Baby, Ashly; Jose, Thomas; Krishnan, Smitha; Allesh Sinu, Palatty (2024)
The interplay between forest cover and pollinator abundance in agricultural landscapes is critical for sustaining biodiversity and ecosystem services, particularly in homesteads that rely on pollination for food production. Forests act as reservoirs of biodiversity, offering essential habitats, floral resources, and ecological connectivity that benefit pollinators.